The Influence of Rewards and Work Motivation on the Performance of Allianz Insurance Agents in an Islamic Economic Perspective - Rachmawati, Putri; Asriani; Femci Purnamasari (HM Publisher, 2021)
Insurance is critical need for the community to prepare for what happens in the future such as critical illness, accidents, pension funds and death. The insurance company appreciates the contribution made by the agent by providing rewards, be it in the form of financial, non-financial as well as in the form of other benefits. Rewarding has a positive purpose, but the problem is that giving rewards has the opposite effect. Agents who only focus on the rewards they can get and only give importance to this allows agents to tend to focus on the result without paying attention to the behaviour and processes in it. This study aims to determine the effect of reward and work motivation on agent performance in the Lampung branch of Allianz Life Indonesia insurance. This research is an observational study where primary data is obtained from interviews and questionnaires, and secondary data is obtained from documentation data. The population in this study were 30 insurance agents, with consecutive sampling technique—data obtained by using a questionnaire to 30 agents. Interviews were conducted with the Head of Agency and Business partners. Based on the results of this study, that reward has a significant effect on the performance of the insurance agent Allianz and work motivation has a significant effect on the performance of the insurance agent Allianz. Based on the principles of shari'ah, the principle of ta'awun (help each other), that is, insurance participants help each other (ta'awun) by collecting a grant called tabarru'.